Measurement of ultralow gate tunneling currents using floating-gate integrator technique - Paulsen, Ron (IEEE Electron Device Letters, 2005)
We report for the first time that a gate tunneling current measurement sensitivity better than 3/spl times/10/sup -22/ A has been achieved by using a floating-gate integrator technique. The technique involves monitoring the charge change in the floating-gate integrated with an on-chip op-amp and an on-chip feedback capacitor. We used this technique to study the stress-induced leakage current (SILC) and its cycling dependence of 70 /spl Aring/ oxides in the direct tunneling region at oxide voltage as low as 1.9 V. The technique has been validated through correlation to direct measurement on MOSFET arrays and theoretical calculations. The measured SILC current is modeled with an Inelastic trap-assisted tunneling model.